Solid waste management beliefs and practices in rural households towards sustainable development and pro-environmental citizenship - M.R. Limon; J.P.C. Vallente; N.C.T. Corales (Global Journal of Environmental Science and Management)
This study examined the waste management beliefs and practices of selected households in a Philippine rural municipality.  The sample used for this study involved rural families comprising of 332 households, which was drawn from the population using multistage cluster unequal allocation sampling technique. Descriptive statistics was used to analyze data gathered. Findings show that households encountered many problems when it comes to practicing traditional and modern ways of solid waste management. Moreover, it was revealed that participants were ill-informed about the various aspects of waste management, and that there was little reuse and recycling of waste materials among the households. In terms of the participants’ solid waste management beliefs, their ratings yielded a X̄ score of 1.08, which means that they generally have positive beliefs towards managing household wastes. When it comes to their practices, participants obtained a X̄ score of 2.59, suggesting that the selected households apply, to certain degrees, various acceptable waste disposal measures. Nevertheless, they also demonstrated beliefs and practices that were not environment friendly. From these findings, this study proposed a plan of solid waste management activities for households, which was collaboratively assessed by local government authorities. The proposed plan was unanimously accepted by the evaluators, who approved of the intervention’s wide-scale implementation in the province. A number of significant implications were offered in this study, such as conducting community workshops and campaigns for the effective management of solid wastes.